Determining Nurses' Praetorianist Leadership Behaviors: A Descriptive Study. - Cetin, Yasin (International Journal of Caring Sciences)
Background: Manager nurses use certain managerial strategies while ensuring the coordination of nursing work in busy and fast-paced working conditions. Leadership styles play an important role in these strategies. Objectives: It was aimed to determine the praetorianistic leadership behavior styles of nurse executives within the scope of this research. Methods: The target population of the research consisted of 575 nurses. The research was of quantitative pattern and descriptive type. A 9-item demographic information form and 21-item praetorianistic leadership scale were used in the research. Data were collected online between September and November 2021. Normality tests, t test and analysis of variance (ANOVA) were used to analyze the data. Results: It was determined that the nurses' age, education level, working year and the units they worked in showed a statistically significant difference with praetorianistic behaviors. (p < .05). Conclusion: It has been determined that praetorianistic leadership behavior in nurses increases as the age and seniority of the nurses increase. It was found that praetorianistic leadership decreased as the education level of nurses increased, while praetorianistic behaviors increased in intense and stressful working environments. Impact Statement: It is thought that it can help reduce communication problems, conflicts or negative behaviors in the organization by providing praetorianism behavior awareness in the management of nursing services.